TECHNOLOGIES FOR TEACHER TRAINING FOR INCLUSIVE EDUCATION IN THE PROCESS OF CONTINUOUS PROFESSIONAL DEVELOPMENT - Rizayeva Shalola Mamir kizi (Bright Mind Publishing, 2025)
This article analyzes the technologies for preparing teachers for inclusive education within the framework of the continuous professional development system. The issues of forming inclusive competencies of teachers through modern technologies, module-based training, practical exercises and trainings in the process of professional development are highlighted. Also, suggestions and recommendations are given based on international experience and existing approaches in Uzbekistan.
Keywords: Inclusive education, teacher training, professional development, technology, competence, training, module.